Father's Perspective in Caring for Babies and Toddlers to Prevent Stunting - Juli Oktalia; Ni Gusti Made Ayu Agung Budhi; Ferina Ferina (Jurnal Ilmu dan Teknologi Kesehatan)
Background: Stunting is a condition where the height of children under five years of age is far below the age standard due to chronic malnutrition and other health problems. According to data from the World Health Organization (WHO) and various national health institutions, stunting can have a long-term impact on children's cognitive development, health and well-being. Traditionally, the role of childcare is often considered the mother's responsibility, while the father's role is often focused on financial aspects. Objective: to obtain information about fathers' perspectives in caring for babies and toddlers to prevent stunting. Method: This research is qualitative research involving 96 father respondents. The inclusion criteria for fathers were fathers who were healthy and had children aged infants or toddlers. Results: From this study it was still found that the majority showed sufficient awareness of the importance of nutrition for their children, but their knowledge was often limited to basic information and did not fully understand the details of a proper diet or the importance of regular health checks. Fathers' involvement in health visits and child health consultations is often more limited. Fathers tend to rely on mothers for decisions regarding health and treatment, despite fathers' awareness of the importance of routine check-ups and immunizations. Conclusion: the father's role cannot yet be said to be optimal to help prevent stunting because there are still values ​​that assume this function lies with the mother. There is a need to increase the optimization of the father's role in addition to increasing knowledge capacity.